Virgin Coconut Oil Ameliorates Cognitive Impairment in Alzheimer’s-Like Rats Induced with Aluminium Chloride (AlCl₃) + D-Galactose (D-Gal) - Mahdi, Onesimus; Benjamin, Simeon; Bobbo, Khadijat Abubakar; Agbon, Abel Nosoreme; Aliyu, Lawan Ibrahim; Mathias, Kuchahyells; Alhassan, Anathoth; Dilla, Deborah; Reseph, Raphael (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Neurodegenerative diseases are a group of disorders marked by the progressive deterioration of neurons in the brain and spinal cord, with age-related cognitive dysfunctions, particularly in Alzheimer’s disease (AD) strongly associated with neurotransmission abnormalities. Aluminium (Al), the third most abundant metal in the Earth's crust, is recognized for its neurotoxic properties, while D-galactose (D-gal), a reducing sugar, induces cellular senescence through its interaction with amino acid residues in proteins. The combined administration of Al and D-gal has been established as a model for inducing neurotoxicity and studying AD mechanisms. Virgin Coconut Oil (VCO), a natural supplement rich in medium-chain triglycerides convertible to ketone bodies for cerebral energy metabolism, has demonstrated potential in promoting neurogenesis in aging models. This study investigates the neuroprotective effects of VCO in a rat model of cognitive dysfunction induced by Aluminium Chloride (AlCl₃) and D-gal. Thirty-five healthy male albino Wistar rats (150–200 g) were administered D-gal (60 mg/kg, intraperitoneally) and AlCl₃ (200 mg/kg, orally). Rats in treatment groups received VCO at doses of 1 and 3 ml/kg/day, while a positive control group was treated with donepezil (1 mg/kg) alongside AlCl₃ and D-gal. Cognitive performance was assessed using the Novel Object Recognition test; oxidative stress was evaluated by measuring hippocampal malondialdehyde (MDA) levels, and histological analysis of the CA1 region was conducted to assess neuronal integrity. Rats exposed to AlCl₃ and D-gal exhibited significant cognitive deficits, elevated MDA levels, and hippocampal neuronal loss (p < 0.05). VCO administration significantly attenuated these impairments by reducing oxidative stress and preserving hippocampal cytoarchitecture. These findings suggest that VCO possesses neurotherapeutic potential for mitigating AD-related cognitive impairments.